A comparative analysis of the NaI detector response function using GAMOS and FLUKA Monte Carlo simulations - A. Arectout; H. Boukhal; E. Chakir; M. Jarmouni; M. Assalmi; T. El Ghalbzouri; O.E. Belhaj; Mohamed Drissi El-Bouzaidi; A. Nouayti; I. Zidouh; H. El Yaakoubi (Nuclear Analysis)
This work aims to study the response function of a 2″×2″ NaI(Tl) scintillation detector using Monte Carlo simulations. A precise mathematical model of the NaI(Tl) scintillator was developed using both FLUKA and GAMOS Monte Carlo simulation software. The photon pulse height distributions of the NaI(Tl) without influence of its energy resolution, obtained with FLUKA and GAMOS codes, were converted into a real NaI(Tl) response function using the necessary conversion process. Spectral characteristics such as full-energy peak efficiency, energy resolution, peak-to-Compton ratio, and peak-to-total ratio were investigated by simulation at different gamma-ray energy obtained from 109Cd, 137Cs, 54Mn, 65Zn, and 60Co sources. The simulated spectra from the GAMOS code were consistent with those generated by the FLUKA code. Additionally, the comparison between simulated results and experimental data demonstrated good agreement. The validation of the computational models used for the NaI(Tl) detector in both FLUKA and GAMOS software was successfully achieved, confirming the accuracy of the simulations in replicating the detector's response.